2016
DOI: 10.1111/jzo.12315
|View full text |Cite
|
Sign up to set email alerts
|

Is isolation by distance the cause of the genetic structure of the Iberian white‐throated dipper populations?

Abstract: Population fragmentation in animals, by influencing dispersion between regions, may cause so‐called isolation by distance (IBD). The genetic structure of the white‐throated dipper Cinclus cinclus populations in the Iberian Peninsula was analysed using microsatellites. Birds (n = 226) were sampled during 2000–2012 from 12 major populations of the dipper' distribution range in the Iberian Peninsula. At the eight loci studied, 113 alleles were found. Three population groups were identified: the first comprises Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Geographic isolation has long been considered an important factor in biological diversification and speciation (Slatkin, 1987; Wang & Summers, 2010), and was found to drive genetic divergence in many species, such as fishes (Collin & Fumagalli, 2015), reptiles (Rodrigues & Diniz‐Filho, 2017), birds (Hernández, Campos, Santamaría, Rojo, & Dias, 2016; Seeholzer & Brumfield, 2018), and mammals (Kierepka & Latch, 2016; Puechmaille et al., 2011). In the present study, a significant positive correlation was observed between geographic distance and nuclear divergence (Tables 2 and 3), and the results of causal models revealed the main role of geographic isolation in intraspecific nuclear divergence of R. episcopus (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Geographic isolation has long been considered an important factor in biological diversification and speciation (Slatkin, 1987; Wang & Summers, 2010), and was found to drive genetic divergence in many species, such as fishes (Collin & Fumagalli, 2015), reptiles (Rodrigues & Diniz‐Filho, 2017), birds (Hernández, Campos, Santamaría, Rojo, & Dias, 2016; Seeholzer & Brumfield, 2018), and mammals (Kierepka & Latch, 2016; Puechmaille et al., 2011). In the present study, a significant positive correlation was observed between geographic distance and nuclear divergence (Tables 2 and 3), and the results of causal models revealed the main role of geographic isolation in intraspecific nuclear divergence of R. episcopus (Table ).…”
Section: Discussionmentioning
confidence: 99%